Relevance for food sciences of quantitative spatially resolved element profile investigations in wheat (Triticum aestivum) grain - Pongrac, Paula (The Royal Society, 2013)
Bulk element concentrations of whole grain and element spatial distributions at the tissue level were investigated in wheat (Triticum aestivum) grain grown in Zn-enriched soil. Inductively coupled plasma mass spectrometry and inductively coupled plasma optical emission spectrometry were used for bulk analysis, whereas micro-proton-induced X-ray emission was used to resolve the two-dimensional localization of the elements. Soil Zn application did not significantly affect the grain yield, but did significantly increase the grain Ca, Fe and Zn concentrations, and decrease the grain Na, P and Mo concentrations; bulk Mg, S, K, Mn, Cu, Cd and Pb concentrations remained unchanged. These changes observed in bulk element concentrations are the reflection of tissue-specific variations within the grain, revealing that Zn application to soil can lead to considerable alterations in the element distributions within the grain, which might ultimately influence the quality of the milling fractions. Spatially resolved investigations into the partitioning of the element concentrations identified the tissues with the highest element concentrations, which is of utmost importance for accurate prediction of element losses during the grain milling and polishing processes.